A Study of Morbidity Pattern Among Construction Workers in Kalaburagi, North Karnataka, India - Deshmukh, Sunil A; Ghooli, Shreeshail (National Journal of Community Medicine, 2015)
Background: Construction sector is a booming industry in India and the labours are susceptible to various health and occupational hazards as these workers work in dusty environment and it is an unorganized sector scattered all over India. Method: A cross sectional study was carried out at various con- struction sites in Kalaburagi, Karnataka. Study included 150 male workers. Detailed socio-demographic information was collected on a pre-designed and pre-tested questionnaire. Results: Of the 150 workers (all males) examined, (80%) belonged to 15-45 years age group. Highest morbidity was seen in the form of cough 72.55%, musculoskeletal complaints 60.78%, followed by breathlessness 47.05%, skin problems 39.22% and chest pain com- plaints 39.22%. Conclusion: The present study concluded that the workers in this industry are exposed to stone dust which leads to various morbid- ities especially respiratory and skin problems and heavy work leading to musculoskeletal problems. These problems are signifi- cantly associated with duration of exposure.